The power of you! : - Martineau, Scott (John Wiley & Sons, 2006)
Martineau is with Conscious One, the largest Internet resource for inspirational tools, products, and online interactive courses for personal growth and enlightened spirituality. He offers interested general readers a self-help text for balancing the pressures of work and the needs of one's personal life. The text combines practical tools, techniques, and skills with inspirational and practical advice from renowned contributors such as Dr. Nathaniel Branden, Arthur Joseph, Joe Vitale, and Jack Canfield.